Investigation of the relationship between humor use and psychological resilience of mothers with special needs children - ÇAYAK, SEMİH (My University, 2023)
Mothers of children with special needs have various difficulties, mostly as direct caregivers of the child. The level of coping with these difficulties is also related to the psychological resilience of mothers. Although there are many coping mechanisms to protect the psychological resilience of people, humor is one of them. For this purpose, it was aimed to examine the relationship between the levels of coping with humor and psychological resilience of mothers who have children with special needs. The study group of this research, which was designed according to the relational survey model, consisted of 480 mothers with children with special needs, whose educational examinations were completed by applying to various Guidance and Research Centers in Istanbul in the spring semester of the 2022-2023 academic year. In the study, Coping with Humor Scale and Brief Psychological Resilience Scale were used as data collection tools. In the study, the relationships and differences between the variables were examined through the ANOVA test, Pearson correlation coefficient and regression analysis. As a result of the correlation analysis, it was found that there was a positive, moderate, and significant relationship between the mothers' scores on coping with humor and psychological resilience scores. As a result of the regression analysis, it was found that the level of coping with the difficulties brought by this situation through humor predicts the psychological resilience of mothers who have children with special needs. As a result of the study, it was seen that humor is an important coping tool in increasing the psychological resilience of mothers with children with special needs, and various suggestions were made for educators and mental health professionals.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Eğitim Yönetimi ve Teftiş; Social Sciences and Humanities; Education; Educational Sciences; Administration and Supervision in Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Individuals with special needs; Psychological resilience; Coping through humor; Mothers of individuals with; special needs